Two cases of neonatal hyperglycemia caused by a homozygous COQ9 stop‐gain variant - Russell Donis; Maryam Al Badi; Nadia Alhashmi; Andrew T Hattersley; Sarah E Flanagan; Elisa De Franco (Journal of Diabetes Investigation)
ABSTRACT Neonatal diabetes mellitus (NDM) is a monogenic condition diagnosed <6 months of age with >40 genetic causes. International guidelines recommend referral for genetic testing immediately after diagnosis since the genetic result guides clinical management. We used next‐generation sequencing to identify a homozygous pathogenic variant, p.(Arg244*), in COQ9 in 2 individuals referred for NDM testing. Both had insulin‐treated hyperglycemia, severe structural brain defects, dysmorphic features, and lactic acidosis. Recessive loss‐of‐function variants in COQ9 cause Coenzyme Q10 deficiency‐5, a multi‐system mitochondrial disease, with 7 cases reported. Neonatal hyperglycemia has not been reported in any of these cases but has been described for two other Coenzyme Q10 disorders caused by variants in COQ2 and COQ4. Our report shows that individuals with COQ9‐related disease can present with neonatal hyperglycemia, expanding the clinical spectrum of this disorder. We recommend the inclusion of COQ9, as well as COQ2 and COQ4, to gene panels used for NDM testing.